The effect of capsicum frutescens-l to transient receptor potential vinaloid-1, toll like receptors (tlr-4) and interleukin 1 beta (il-1Î²) on periodontitis - Jenny Sunariani; Latief Mooduto; Yuliati Yuliati (DiscoverSys Inc., 2017)
Objective: Indonesia has many kinds of useful herbs, which are often used as species such as chili, pepper or cayenne pepper (Capsicum frutescens L). Previous study showed topical capsaicin can be used as a therapy to cure pain due to inflammation. Small concentrations of capsaicin can attenuate cytokines in the inflammatory process. Capsaicin studies in animal model showed activation of the transient receptor potential vanilloid-1. Capsaicin can decrease various cytokines such as IL-6, IL-12, IL-1Î², and increase IL-10. Capsaicin is a natural agonist for transient receptor potential vanilloid-1. The aim of this study is to prove the effect of capsaicin on transient receptor potential vanilloid-1 expression and TNF-Î± and TLR-4 toward pain.Material and Methods: An experimental laboratory research used animal model Wistar male rats (Rattus novegicus) induced with Aggregatibacter actinomycetemcomitans serotype b and green chili extract (Capsicum frutescens L.) with a dose of 0.0912 mg/kg/day was applied to surface of the gingiva on maxillary first molar for 7 days. An immunohistochemical examination was conducted to see the density of transient receptor potential vanilloid-1, and the expression of TLR-4 and IL-1Î² in the mucosal tissues of the oral cavity.Results: There were significant differences in the applications of Capsicum frutescens L. with increasing of TRPV ligand-1 and IL-1Î² (p < 0.05), while the TLR-4 (p > 0.05) showed a significant difference to TRPV-1 and IL-1Î². There is no significant difference to TLR-4.Conclusion: Capsaicin can increase TRPV-1 and decrease IL-1Î² but did not affect the TLR-4. Capsaicin can be used to decrease pain and accelerate healing process in periodontitis.